A Simple Model of Buyer-Seller Networks in International Trade - Philipp Herkenhoff; Sebastian Krautheim; Philip Sauré (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The recent literature on firm-to-firm trade has documented salient empirical regularities of the buyer-seller network. We propose a simplistic re-interpretation of the classical Krugman (1980) model that accounts for surprisingly many of the empirical regularities. This re-interpretation relies on randomized bundling of Krugman-varieties into heterogeneous firms, economically neutral `sales units' that import foreign varieties but belong to local firms, and a statistical reporting threshold that applies to firm-to-firm transactions. We argue that our model provides an important benchmark for the assessment of theoretical models that aim to identify the determinants of firm-to-firm networks.
Keywords: F10; F12; F14; 330; firm-to-firm; buyer-seller; trade; network; random matching